(untitled) (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2024)
The issue of discipline was very important for early modern armies. Considering the usual social background of soldiers, them being a surplus of the rural population, social outcasts, criminals who joined the army as a way to commute their sentences, or other “undesirables”, the discipline was very harsh, sometimes bordering on inhumane. On top of that, the harsh conditions of the 17th century warfare led to further brutalisation of soldiers, which in turn necessitated tighter control over them. In this paper, we will analyse the disciplinarian problems faced by the Imperial forces on the Rhine front during the Nine Year’s War (1688-1697), especially during the period of command of Prince Louis William, Margrave of Baden-Baden (1693-1697).